RESPONDING TO REFUGEES DURING THE COVID-19 PANDEMIC IN INDONESIA: A FOCUS ON ROHINGYA REFUGEES IN LHOKSEUMAWE, ACEH 2020-2022 - Fajri, Muhammad; Putra Disantara, Fradhana; Mukammil, Miftah Mardhatillah (Universitas Syiah Kuala, 2024)
This study examines the roles of UNHCR, the government, and health authorities in addressing the needs of refugees during the COVID-19 pandemic. It specifically looks at national regulations concerning vaccinations for refugees and identifies the obstacles and challenges in providing these vaccinations. The findings indicate that the collaboration among UNHCR, the government, and health services in managing refugee issues has not been effective. Despite 120 refugees arriving in Lhokseumawe City, the available shelter was inadequate. Furthermore, UNHCR fell short in conducting PCR tests, distributing masks and hand sanitizers, and ensuring vaccinations for the refugees. National regulations regarding the vaccination of Rohingya refugees are stipulated in Article 27 of the 2016 Presidential Regulation on Handling Refugees from Abroad. The administration of vaccinations to refugees has faced challenges due to logistical constraints and shortages in vaccine supplies. To address these issues, the study suggests the need for additional adequate shelters for refugees, as well as the provision of masks and hand sanitizers. It also recommends implementing PCR testing for all refugee activities and finding administrative solutions to facilitate vaccine access for refugees.